Evolution of the stress-strain state and the dynamics of the Skip cover of the Ukrainian Carpathians - O.B. Gintov; I. N. Bubnyak; Yu. M. Vikhot'; A. V. Murovskaya; M. V. Nakapeluch (Геофизический журнал, 2011)
New results of interpretation of tectonophysical investigations of the flysh deposits in the Skyba nappe of the Ukrainian Carpathians carried out in four areas in its northwestern and central parts are presented. Complex application of structural - paragenetic and kinematic analyses helped to synchronize three parameters - time of deformation, azimuths of the main axes of stresses orientation and deformation modes for prefolding, folding and postfolding stages of development of the outer part of the Ukrainian Carpathians. It has been proved that thrust shear strain was coeval with strike-slip that provided the rapid advancement of the thrust front. The role of normal faulting with о 3 axis stretching of northeastern and northwestern orientations has been shown. It is assumed that the mentioned deformations had relatively young age. Formation of the Skyba nappe structure is related to the development of the Western and Southern Carpathians. In the global scale the activity of the tangential forces of northwestern and sub-longitudinal directions is explained by the convergence of the Adriatic and European microplates and also the African-Arabian and Eurasian mega-plates.